DUFTEN AF DANSKHED - Katz, Joel (Tidsskriftet Antropologi, 2000)
The scent of Danishness is attempted at being discerned. In doing so, the term "culture scent set" as an analytical concept is coined. It is defined as the specific conglomerate of aromatic elements in a culture: racial scents (contingent upon body hair, fatty skin tissues, type of hair, and diet), clothing textiles, building materials, aromas used in the home and the surrounding natural environment. Recent changes in the Danish language regarding "scent" are discussed semiotically as representations of changes in attitudes concerning olfaction, especially a growing conscious awareness of fragrance in defining Danishness. Lastly, the con-temporary scent of Danishness is decribed as a dynamic expression of certain basic yet ever-changing culture-bound essences.